ULTRASOUND-ASSISTED MICROWAVE SYNTHESIS AND MECHANISTIC ASPECT OF 2-AMINO-4, 6-DIARYL PYRIMIDINES AND 3, 5-DIARYL-1H- PYRAZOLES - Elzupir, Amin O.; Saeed, Ahmed E. M.; BARAKAT, IZZELDEEN E.; Westhuizen, Jan H. Van Der (International Journal of Current Pharmaceutical Research, 2015)
A novel approach have been developed for synthesis of a series of 2- amino 4,6- diaryl pyrimidines and 3,5-diaryl -1H- pyrazoles, using a condensation reaction of guanidine or hydrazine with enones compounds, in the presence of ethanol as solvent and NaOH as catalyst. Ultrasound was used for solvation of the enones, followed by microwave for heterocyclization reaction. A moderate to good yield has been gotten in a short period of time. The structures of synthetic compounds have been elucidated by 1H NMR, EI-MS, FT-IR and UV-Vis spectroscopy. Moreover, the mechanism of reaction was investigated, the products were formed through direct addition to hard electrophile followed by heterocyclization.